1986
DOI: 10.1037/h0080093
|View full text |Cite
|
Sign up to set email alerts
|

The suffix effect and preattentive unit-formation in visual short-term memory.

Abstract: Immediate ordered recall of digits from visual short-term memory was tested, primarily using a long-exposure (approximately 3^ sec) visual presentation during which subjects spoke aloud (articulatory suppression). A to-be-ignored digit placed to the right of the visual presentation, called a suffix, impaired recall approximately one digit, suggesting that the suffix could not be excluded from visual short-term memory. The suffix effect was attenuated when the suffix was segregated from the to-be-recallcd digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
1
17
1
Order By: Relevance
“…Immediately following presentation, the subjects recalled the letters in serial order. Frick (1985;Frick & DeRose, 1986) had previously found that preventing subvocalization of visually presented list items tended to induce reliance on a visual code. The subjects in this experiment were therefore required to silently mouth the syllable "blah" during all conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Immediately following presentation, the subjects recalled the letters in serial order. Frick (1985;Frick & DeRose, 1986) had previously found that preventing subvocalization of visually presented list items tended to induce reliance on a visual code. The subjects in this experiment were therefore required to silently mouth the syllable "blah" during all conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, Greene (1987) failed to replicate the visual suffix effects documented in each of three previous reports (Frick & De Rose, 1986b;Hitch, 1975;Kahneman, 1973). Even had the effects been replicated, it can be argued that the findings documented in the three reports do not seriously challenge bottom-up, overwriting accounts of the suffix effect (see Crowder, 1986;Greene, 1987).…”
mentioning
confidence: 71%
“…The to-be-remembered items were the digits 0-9, except for 3, which, following LeCompte and Watkins (1995) and Frick and De Rose (1986b), was reserved for use as the suffix. A separate set of 63 digit lists was constructed for each participant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations